PELATIHAN SOLIDWORKS UNTUK MENINGKATKAN PENGETAHUAN MECHANICAL DESIGN ASSOCIATE PADA SISWA SMKN 2 BANDUNG - Budi Triyono; Destri Muliastri; Devi Eka Septiyani A; Heri Widiantoro; Rudy Yuni W (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
One of the competencies needed by technicians and engineers in the field of mechanical engineering is to be able to master software engineering in the design and design of a product. CAD (Computer Aided Design) is a computer application in design activities. Students of SMKN 2 Bandung, one of the vocational schools that has a Department of Drawing Engineering. Students of SMKN 2 Bandung already know material related to CAD but still do not know about Solidworks software, this is because there is no licensed software available at SMKN 2 Bandung. The Department of Mechanical Engineering, Politeknik Negeri Bandung, has licensed Solidworks software and provides SolidWorks certification. So based on this issue, Solidworks knowledge improvement was carried out At SMKN 2 Bandung. The purpose of this activity is to improve the competence of Human Resources and increase competitiveness, especially in the millennial generation. The training process begins with a pre-test that aims to measure the initial level of knowledge of SMKN 2 Bandung students related to Solidworks Software, then the introduction and material related to Solidworks, and at the end of the training an evaluation is carried out with a CSWA Trial Exam, and a post-test. The results of the training that has been carried out on 15 participants, show an improvement in the mastery of CAD Solidworks software.